2015
DOI: 10.1159/000369536
|View full text |Cite
|
Sign up to set email alerts
|

Novel Treatments for Celiac Disease: Glutenases and Beyond

Abstract: Currently, the only effective treatment for celiac disease is a strict lifelong gluten-free diet. However, gluten-free dieting is restrictive, difficult to maintain and nutritionally less than optimal. The improved knowledge on celiac disease pathogenesis has enabled researchers to suggest alternative strategies to treat the disorder. The drug development poses a challenge as any novel drug for celiac disease should be simultaneously effective and as safe as the gluten-free diet. The rationale behind enzyme su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
(37 reference statements)
1
10
0
4
Order By: Relevance
“…Metabolic studies under simulated gastrointestinal conditions showed that gluten derived from such plants contain significantly less immunogenic peptides than control plants. Together, our results propose a new way of treating celiac disease and thus underscore the commercial viability of the combination enzyme therapy (Kaukinen and Lindfors 2015). …”
Section: Introductionsupporting
confidence: 53%
“…Metabolic studies under simulated gastrointestinal conditions showed that gluten derived from such plants contain significantly less immunogenic peptides than control plants. Together, our results propose a new way of treating celiac disease and thus underscore the commercial viability of the combination enzyme therapy (Kaukinen and Lindfors 2015). …”
Section: Introductionsupporting
confidence: 53%
“…Currently, following the gluten-free diet for life is the only treatment for celiac disease, although medications may become available in the future (36). The gluten-free diet involves the complete avoidance of wheat, rye, barley, and regular oats.…”
Section: The Gluten-free Diet For Lifementioning
confidence: 99%
“…Çölyak hastalarında glutensiz diyet çok iyi planlansa da uyum ile ilgili sorunlar yaşanmaktadır. Hastalarda diyete uyumsuzluk % 20-80 arasında değişmektedir (15,45). En önemli uyumsuzluk nedenlerine bakıldığında; GFD sosyal yaşamı sınırlamakta, sınırlı besin alımı, glutensiz ürünlerin tatlarının farklı ve pahalı olması, uzun süreli takiplerinin zorlukları, diyet eğitimlerinin yetersizliği ve küçük miktarda bile gluten ihtiva eden besinlerin tüketiminin klinik atakları tetiklemesi olarak sıralanabilir.…”
Section: Glutensiz Diyete Uyumunclassified
“…En önemli uyumsuzluk nedenlerine bakıldığında; GFD sosyal yaşamı sınırlamakta, sınırlı besin alımı, glutensiz ürünlerin tatlarının farklı ve pahalı olması, uzun süreli takiplerinin zorlukları, diyet eğitimlerinin yetersizliği ve küçük miktarda bile gluten ihtiva eden besinlerin tüketiminin klinik atakları tetiklemesi olarak sıralanabilir. Yaşam tarzı değişiklikleri hem çocuk hem de ailede oluşmadığından da diyete uyum olumsuz etkilenmektedir (45,46).…”
Section: Glutensiz Diyete Uyumunclassified